Poverty Reduction and Growth : Virtuous and Vicious Circles - Perry, Guillermo E.; Arias, Omar S.; López, J. Humberto; Maloney, William F.; Servén, Luis (2012)
Poverty Reduction and Growth is about the existence of these vicious circles in Latin America and the Caribbean about the ways and means to convert them into virtuous circles in which poverty reduction and high growth reinforce each other. This publication is organized as follows: Chapter 1: From vicious to virtuous circle; Chapter 2: Dimensions of well-being, channels to growth; Chapter 3: How did we get here? Chapter 4: The relative roles of growth and inequality for poverty reduction; Chapter 5: Pro-poor growth in Latin America; Chapter 6: Does poverty matter for growth? Chapter 7: Subnational dimensions of growth and poverty; Chapter 8: Microdeterminants of incomes: labor markets, poverty, and traps?; and Chapter 9: Breaking the cycle of underinvestment in human capital in Latin America.